Fabrication and characterization of bioactive zirconia-based nanocrystalline glass-ceramics for dental abutment. Issue 19 (1st October 2021) - Li, Bo; Xu, Guofu; Wang, Bohan; Huang, Jiwu; Engqvist, Håkan; Xia, Wei; Fu, Le
Abstract: Zirconia-based ceramics are becoming a popular biomaterial in dental implantology due to their natural silver-white color, excellent mechanical properties, and good biocompatibility. However, zirconia-based ceramics are biologically inert, which limits their ability to integrate with the surrounding human tissues. To solve this problem, the bioactive elements of calcium (Ca) and phosphorus (P) were doped in high-strength ZrO2 –SiO2 nanocrystalline glass-ceramics (NCGCs) to overcome the biological inertness of ZrO2 -based ceramics. XRD results showed that tetragonal zirconia (t-ZrO2 ) and monoclinic zirconia (m-ZrO2 ) were the only two crystalline phases after spark plasma sintering. Ca and P dopants acted as destabilizer of t-ZrO2, enhancing its transformability to m-ZrO2 during sintering. The amount of t-ZrO2 exerted significant effects on the average flexural strength of the NCGCs. The NCGC with 45 mol% ZrO2 were composed of 64.5 vol% t-ZrO2 and 35.5 vol% m-ZrO2 after sintering at 1230 °C. And, the average flexural strength and Vickers hardness of the NCGC was 615 MPa and 1049 HV, respectively. In comparison, the NCGC with 65 mol% ZrO2 were composed of 12.6 vol% t-ZrO2 and 87.4 vol% m-ZrO2 after sintering at 1150 °C. The average flexural strength and Vickers hardness of the NCGC was 293 MPa and 839 HV, respectively. Interestingly, the NCGCs exhibited a plastic deformation behavior during flexural strength test, which was different from traditional brittle ceramics. The ion release results demonstrated that Ca 2+ and Si 4+ ions kept on releasing from the surface of the material. The formation of hydroxyapatite in the in-vitro apatite formation test indicated that the NCGCs had good biological activity. The doped ZrO2 -based NCGCs combined moderate strength and good bioactivity. Hence, the NCGCs show promising potential to be used in sub-gingival regions, such as dental abutments.